Research progress on hippocampal neurogenesis in autism spectrum disorder - Mengxiang Chen; Lanmin Guo; Qinghong Li; Shunbo Yang; Wei Li; Yanmei Lai; Zhihai Lv (Wiley, 2024)
ABSTRACT Autism spectrum disorder (ASD) is a group of severe neurodevelopmental disorders with unclear etiology and significant heterogeneity that is emerging as a global public health concern. Increasing research suggests the involvement of hippocampal neurogenesis defects in the onset and development of ASD, drawing increasing amounts of attention to hippocampal neurogenesis issues in ASD. In this paper, we analyze relevant international studies on hippocampal neurogenesis in ASD, discuss the role of neurobiology in the pathogenesis of ASD, and explore the potential of improving hippocampal neurogenesis as a therapeutic approach for ASD. This review aims to provide new treatment perspectives and theoretical foundations for clinical practice.